CARRYING CAPACITY ANALYSIS OF CROSSED CYLINDRICAL ROLLER SLEWING BEARING UNDER COMBINED LOADS - LI YunFeng; JIANG Di; CHENG YaBing (Jixie qiangdu)
The mechanics model of crossed cylindrical roller slewing bearing under combined radial,axial and tilting moment loads was established,this model considers the clearance parameter of the slewing bearing. The mechanics model was numerically solved by using Newton-Raphson method. Two carrying capacity indexes that are safety factor and fatigue life of the slewing bearing were calculated,and the influence law of slewing bearing clearance on the internal load distribution,safety factor and fatigue life of the slewing bearing was analyzed. The results show that the change of slewing bearing clearance has significant influence on the internal load distribution and carrying capacity of the slewing bearing. With the increase of axial clearance of slewing bearing,the number of rollers inside the slewing bearing undertaking the external load decreases gradually,the load of the heaviest loaded rollers increases correspondingly. During the process of the axial clearance increase of the slewing bearing from 0 mm to 0. 24 mm,the carrying capacity safety factor of the slewing bearing decreases by 16 percent,the fatigue life decreases by 26 percent.